Innovative Service Experience and Revisit Intention in Community Banking: The Mediating Roles of Satisfaction and Authenticity Evidence from PT BPR Bank Bantul, Indonesia - Kurniawan, Rangga Muhammad; Purwoko, Purwoko; Setiawan, Zunan (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study examines how innovative service experiences shape customers’ intentions to revisit a community bank, with a focus on the mediating roles of authenticity and satisfaction. Drawing on data from 447 customers of PT BPR Bank Bantul (Perseroda) in Yogyakarta, Indonesia, the research operationalises Creative Service Experience (CRTE), Authenticity (AUTH), Memorability (MEM), Satisfaction (SATF), and Revisit Intention (BV) and tests a theoretically grounded causal model using PLS-SEM. Results show that seven of nine hypothesised paths are supported. CRTE strongly fosters perceptions of authenticity (β ≈ 0.49, t = 10.419, p < 0.001) and creates memorable experiences (β ≈ 0.60, t = 14.183, p < 0.001), and it also contributes to satisfaction (β ≈ 0.25, t = 4.887, p < 0.001). However, CRTE and MEM do not exert significant direct effects on revisit intention (CRTE → BV: β ≈ 0.05, t = 1.038, p = 0.299; MEM → BV: β ≈ 0.02, t = 0.348, p = 0.753). Instead, satisfaction emerges as the principal conduit to behavioural intent: satisfaction has the largest direct influence on revisit intention (β ≈ 0.51, t = 5.516, p < 0.001). Authenticity also contributes directly to both satisfaction and revisit intention (AUTH → SATF: β ≈ 0.16, t = 2.658, p = 0.008; AUTH → BV: β ≈ 0.18, t = 2.581, p = 0.010). The structural model explains approximately 60.7% of variance in revisit intention (R² = 0.607).